Damage-responsive elements in Drosophila regeneration - Vizcaya-Molina, Elena; Klein, Cecilia C.; Serras, Florenci; Mishra, Rakesh K.; Guigó, Roderic; Corominas, Montserrat (Genome Research, 2018)
One of the most important questions in regenerative biology is to unveil how and when genes change expression and trigger regeneration programs. The resetting of gene expression patterns during response to injury is governed by coordinated actions of genomic regions that control the activity of multiple sequence-specific DNA binding proteins. Using genome-wide approaches to interrogate chromatin function, we here identify the elements that regulate tissue recovery in Drosophila imaginal discs, which show a high regenerative capacity after genetically induced cell death. Our findings indicate there is global coregulation of gene expression as well as a regeneration program driven by different types of regulatory elements. Novel enhancers acting exclusively within damaged tissue cooperate with enhancers co-opted from other tissues and other developmental stages, as well as with endogenous enhancers that show increased activity after injury. Together, these enhancers host binding sites for regulatory proteins that include a core set of conserved transcription factors that control regeneration across metazoans.
10.1101/gr.233098.117